48‐2: Design Strategies of Fluorescent Dopants toward Pure Blue for Highly Efficient Top Emission OLEDs. Issue 1 (25th September 2020) - Takahashi, Ryota; Ito, Hirokatsu; Nakano, Yuki; Shirasaki, Yoshinao; Masuda, Tetsuya; Mase, Kazuma; Kawamura, Yuichiro; Kuma, Hitoshi
Abstract : A blue dopant (BD) emitting pure blue fluorescence was created on new design strategies that combined specific partial molecular structures to reduce peak shoulder of the fluorescence spectrum. The top emission organic light emitting diode using the new BD achieved L/J/CIEy=201, which was about 10% higher than the conventional BD.